Cancer stem cell marker DCLK1 reprograms small extracellular vesicles toward migratory phenotype in gastric cancer cells. Issue 13 (28th May 2021) - Carli, Annalisa L. E.; Afshar‐Sterle, Shoukat; Rai, Alin; Fang, Haoyun; O'Keefe, Ryan; Tse, Janson; Ferguson, Fleur M.; Gray, Nathanael S.; Ernst, Matthias; Greening, David W.; Buchert, Michael
Abstract: Doublecortin‐like kinase 1 (DCLK1) is a putative cancer stem cell marker, a promising diagnostic and prognostic maker for malignant tumors and a proposed driver gene for gastric cancer (GC). DCLK1 overexpression in a majority of solid cancers correlates with lymph node metastases, advanced disease and overall poor‐prognosis. In cancer cells, DCLK1 expression has been shown to promote epithelial‐to‐mesenchymal transition (EMT), driving disruption of cell‐cell adhesion, cell migration and invasion. Here, we report that DCLK1 influences small extracellular vesicle (sEV/exosome) biogenesis in a kinase‐dependent manner. sEVs isolated from DCLK1 overexpressing human GC cell line MKN1 (MKN1 OE ‐sEVs), promote the migration of parental (non‐transfected) MKN1 cells (MKN1 PAR ). Quantitative proteome analysis of MKN1 OE ‐sEVs revealed enrichment in migratory and adhesion regulators (STRAP, CORO1B, BCAM, COL3A, CCN1) in comparison to MKN1 PAR ‐sEVs. Moreover, using DCLK1‐IN‐1, a specific small molecule inhibitor of DCLK1, we reversed the increase in sEV size and concentration in contrast to other EV subtypes, as well as kinase‐dependent cargo selection of proteins involved in EV biogenesis (KTN1, CHMP1A, MYO1G) and migration and adhesion processes (STRAP, CCN1). Our findings highlight a specific role of DCLK1‐kinase dependent cargo selection for sEVs and shed new light on its role as a regulator of signaling in gastric tumorigenesis.